Health and Wellbeing Among Nepali Migrants: A Scoping Review - Mahato, Preeti; Bhusal, Susagya; Regmi, Pramod; Teijlingen, Edwin van (Journal of Health Promotion, 2024)
There is limited evidence of research conducted on the health and well-being of Nepali migrants working abroad. This scoping review aims to summarise and synthesise the existing evidence available currently on the health and well-being of Nepali migrants working abroad. A scoping review was undertaken following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews using the five-stage protocol. We searched PubMed, Google Scholar, and NepJol for published international peer-reviewed literature. The database search identified 707 total records published between 2000 to 2022, with 69 of these assessed for eligibility. The quality of the papers was appraised by the JBI Critical Appraisal Tool or the Mixed-Method Appraisal Tool. Thirty-four studies met the inclusion criteria, 13 were qualitative, 19 quantitative, and two were mixed-methods studies. The studies covered a range of subject areas related to Nepali migrants, including their mental health, lifestyle and health-promoting behaviours, work environments and workplace accidents, health problems and access to healthcare services, awareness of sexual behaviours, and perceived risk of sexually transmitted infections and/or HIV. Evidence is scarce on the health and well-being of Nepali migrants who study and work in high-income countries along with the limitation in study design and the methodological rigor. These gaps highlight the need for more extensive, large-scale studies with improved study design across various regions to shed light on the health challenges faced by Nepali migrants.